Salicornia Extract Ameliorates Salt‐Induced Aggravation of Nonalcoholic Fatty Liver Disease in Obese Mice Fed a High‐Fat Diet. Issue 7 (13th June 2017) - Kim, Jae Hwan; Suk, Sujin; Jang, Woo Jung; Lee, Chang Hyung; Kim, Jong‐Eun; Park, Jin‐Kyu; Kweon, Mee‐Hyang; Kim, Jong Hun; Lee, Ki Won
Abstract: High‐fat and high‐salt intakes are among the major risks of chronic diseases including obesity, nonalcoholic fatty liver disease (NAFLD), and nonalcoholic steatohepatitis (NASH). Salicornia is a halophytic plant known to exert antioxidant, antidiabetic, and hypolipidemic effects, and Salicornia ‐extracted salt (SS) has been used as a salt substitute. In this study, the effects of SS and purified salt (PS) on the aggravation of NAFLD/NASH were compared. C57BL/6J male mice (8‐wk‐old) were fed a high‐fat diet (HFD) for 6 mo and divided into 3 dietary groups, which were additionally fed HFD, HFD + SS, and HFD + PS for 13 wk. PS induced aggravation of NAFLD/NASH in HFD‐fed mice. Although the actual salt intake was same between the PS and SS groups as 1% of the diet (extrapolated from the World Health Organization [WHO] guideline), SS induced less liver injury and hepatic steatosis compared to PS. The hepatic mRNA expressions of inflammatory cytokines and fibrosis marker were significantly lower in the SS group than the PS group. Oxidative stress is one of the major causes of inflammation in NAFLD/NASH. Results of the component analysis showed that the major polyphenols that exhibited antioxidant activity in the Salicornia water extract were ferulic acid, caffeic acid, and isorhamnetin. These results suggest that even the level of salt intake recommended by WHO can accelerate the progression of liver disease in obese individuals consuming HFD. It is proposed that SS can be a salt substitute for obese individuals who consume HFD.